Language Attitudes Towards Written English Slang Variety in Internet Social Media - Hamida Halim; Ibrahim Manda; Lababa; Sam Hermansyah (International Journal of Sustainable Applied Sciences, 2023)
This research aims to explore variations in slang English used by social media users and responses using slang English. Social media was the subject of this study such as WhatsApp, Facebook, Instagram and TikTok. A descriptive qualitative method was used in this investigation. The subjects of this research are teenagers or social media/internet users in data collection. The questionnaire approach is the data collection strategy employed in this study, namely by chatting on social media. The questions are based on the questionnaire and carrying out documentation as a complement. In this research, 2 data collection techniques were used, specifically, snowball sampling and purposeful sampling.The data collected was then analyzed based on relevant theories about sociolinguistic studies, and about language attitudes and language variations, especially English slang on social media. The findings in this research show that the English slang most frequently used by respondents on social media is WhatsApp and Instagram. In this case, the slang has four types, namely flippant, imitative, acronym, and clipping. Then the slang English abbreviations that are most widely used on social media are Kepo, DM, Btw, Thx, Otw, Gws, Lol, Pap, Fyi, Guys, and Cod. The reason that makes them interested in using slang on social media is because it is a trend following the times, to make it look cool, not awkward, more familiar with friends, and easy to use among teenagers.